13 ORTHOPEDIC SURGERY ACCESS DISPARITIES FOR MEDICARE AND MEDICAID PATIENTS IN KING COUNTY, WASHINGTON. Issue 1 (1st January 2007) - Poppino, R.; Desnick, L.; Simon, N.
Abstract : Background: Anecdotal evidence suggests that Medicare and Medicaid patients face significant obstacles when seeking nonemergent care from orthopedic surgeons. We have designed a study to investigate whether patients with Medicare, Medicaid, and the uninsured in King County have limited access to orthopedic surgeons compared with their counterparts with preferred provider coverage (PPO). StudyDesign and Methods: Four telephone calls were made to eligible orthopedic practices in King County, WA, seeking an appointment for a fictional patient with various forms of insurance for total knee arthroplasty (TKA) for osteoarthritis. Telephone calls were placed to each of the 96 orthopedic surgeons within these practices to assess which forms of insurance were accepted in their practice and the reasons for these decisions. Eligible orthopedic surgeons and practices were identified using the Washington State Medical Association Web site; surgeons who do not see patients for problems of the knee were excluded. The Centers for Medicare and Medicaid services, as well as a PPO, were contacted to determine physician reimbursement rate for TKA (CPT 27447). Results: One hundred percent of eligible orthopedic surgeons in King County would accept a new patient with a PPO for TKA and 89% would accept new Medicare patients. Thirty-one percent would accept new Medicaid patients. Ninety-seven percent would accept a patient with no insurance for an initial visit, provided that the patient pays at the time of service. Physician responses suggested that the low reimbursement rate is the primary reason for denying or limiting access to Medicare or Medicaid patients. Physician perceptions of Medicaid patients also appear to serve to limit access. These perceptions include beliefs that Medicaid patients generally have poorer health, higher rates of complications, and worse outcomes and are more likely to become involved in legal issues. The maximum physician reimbursement for TKA from Medicare was 1, 225.44; the maximum reimbursement rate from Medicaid was 908.72. In contrast, the maximum physician reimbursement from a PPO was 2, 073.76. Conclusion: Medicare- and PPO-insured patients have roughly equal access to orthopedic surgeons when seeking TKA, whereas Medicaid beneficiaries have significantly less access. Although the uninsured appear to have equal access, the financial costs of physician visits likely serve as a barrier to prevent equal access to orthopedic surgery services. The access gap appears to be a function of low physician reimbursement rates and physician perceptions of Medicaid patients.